Medication related osteonecrosis of jaw in a leukemia patient undergoing systemic arsenic trioxide therapy: A rare case report. (December 2019) - Kumar, Mathangi; Vineetha, Ravindranath; Kudva, Adarsh
Abstract: Osteonecrosis of the jaw is a potential side effect of certain pharmaceutical agents used in the field of medicine. Early diagnosis and effective management of this condition can be challenging to the clinicians. Bisphosphonates and other anti-angiogenic agents are the most common drugs that are attributed to cause medication-related osteonecrosis of the jaw. In the past, arsenic-based compounds were commonly used local agents for pulp devitalization therapy. Arsenic is also one of the components of the chemotherapeutic regimen in the management of refractory leukemia. Although local diffusion of the arsenic compounds is known to cause osteonecrosis, there are no reports of the same caused by its systemic administration. Here, we present the first ever case of mandibular bone necrosis in a patient with acute promyelocytic leukemia who underwent systemic arsenic trioxide therapy.